American Views of the Progressive Catholic Church in Brazil, 1964-1972: From Suspicion to Collaboration (2017)
Both the United States and the Brazilian Catholic Church played decisive roles during the military dictatorship that ruled Brazil between 1964 and 1985. Therefore, an understanding of the relationship between these influential political actors is imperative. This article explores American views of and interests in the Brazilian Catholic Church through a critical examination, categorization, discourse analysis and periodization of cables produced by the U.S. diplomatic mission in Brazil from 1964 to 1972. It maintains that, in the ideological context of National Security doctrine, the U.S. regarded the progressive Catholic movement, and at some level the Church as a whole, as a threat. Nonetheless, starting in 1969, after an intensification of political repression and the growing institutional commitment of the Church to human rights defense, the American approach changed from suspicion to collaboration for development. This article sheds light on the changing political context during the Brazilian military regime.